THE EFFECT OF SERVICE QUALITY ON PATIENT LOYALTY WITH PATIENT SATISFACTION AS A MEDIATION VARIABLE AND SERVICE RATES AS A MODERATING VARIABLE IN LABKESDA, TANGERANG CITY - Anthony Frederick; Fushen (International Journal of Economic, Business, Accounting, Agriculture Management and Sharia Administration (IJEBAS), 2026)
This study aims to analyze the mechanism of patient loyalty formation at the Tangerang City Health Laboratory Technical Implementation Unit (UPT Labkesda) by examining the direct and indirect influence of service quality through mediation of patient satisfaction, as well as the moderating role of service rates. The research method used is quantitative associative causal. Data were collected through questionnaires to 100 respondents with consecutive sampling technique. Data analysis used Structural Equation Modeling based on Partial Least Squares (PLS-SEM). The test results show that: (1) Service quality has a positive and significant effect on patient satisfaction (path coefficient = 0.707; p = 0.000); (2) Patient satisfaction has a positive and significant effect on patient loyalty (path coefficient = 0.255; p = 0.012); (3) Service quality has a strong direct influence on patient loyalty (path coefficient = 0.561; p = 0.000); (4) Patient satisfaction partially mediates the relationship between service quality and loyalty (indirect coefficient = 0.180; p = 0.015); and (5) Service rates significantly moderate and strengthen the relationship between service quality and patient loyalty (interaction coefficient = 0.213; p = 0.007). This model has a predictive power of 69.0% for patient loyalty. These findings confirm that cognitive trust in laboratory technical quality is a major retention factor, and competitive rates serve as a catalyst for strengthening this loyalty.